Configurations on informal habitat in the zone el morro in moravia’s neighborhood (2009)
This article sets out the results of an ethnographic field study done in houses of “El Morro”, an informal settlement of Medellín, before the relocation of its families in social houses, constructed by the State. The aim is to reveal the technical, aesthetic and functional characteristics of the informal housing, in a self-constructed neighborhood by its inhabitants, using for land a waste deposit and as source of construction, the terminal products of the entire city. It exposes cultural patterns that characterizes domestic life in informal habitat; demonstrating the contradictions between the idealized home by official culture and the social realities of the popular homes.